2009
DOI: 10.4137/ijtr.s2318
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Kynurenine Pathway Metabolites on Intracellular NAD+ Synthesis and Cell Death in Human Primary Astrocytes and Neurons

Abstract: The kynurenine pathway (KP) is a major route of L-tryptophan catabolism resulting in the production of the essential pyridine nucleotide nicotinamide adenine dinucleotide, (NAD+). Up-regulation of the KP during inflammation leads to the release of a number of biologically active metabolites into the brain. We hypothesised that while some of the extracellular KP metabolites may be beneficial for intracellular NAD+ synthesis and cell survival at physiological concentrations, they may contribute to neuronal and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 63 publications
(145 reference statements)
1
60
0
Order By: Relevance
“…Anthranilic acid accumulates in the setting of renal failure, and one cell culture study suggested that it might promote renal failure through adverse effects on mesangial cells [16]. In a separate study, treatment of cultured neurons and glial cells with anthranilic acid altered NAD+ levels and caused cytotoxicity [17]. Our metabolite profiling also revealed a drop in acetylglycine, which, like hippurate, is a product of glycine N-acyltransferase and is generated through conjugation of acetyl-CoA and glycine.…”
Section: 4: Discussionmentioning
confidence: 99%
“…Anthranilic acid accumulates in the setting of renal failure, and one cell culture study suggested that it might promote renal failure through adverse effects on mesangial cells [16]. In a separate study, treatment of cultured neurons and glial cells with anthranilic acid altered NAD+ levels and caused cytotoxicity [17]. Our metabolite profiling also revealed a drop in acetylglycine, which, like hippurate, is a product of glycine N-acyltransferase and is generated through conjugation of acetyl-CoA and glycine.…”
Section: 4: Discussionmentioning
confidence: 99%
“…In addition, the KP has been associated with inflammatory responses in different neurological disorders, and this mechanism, which may be inherent to some KP metabolites, could contribute to the neurodegenerative pattern associated with these diseases (Chen et al, 2010;Tan et al, 2012). Some neuroactive metabolites are formed in the KP, including the well-known neurotoxin and glutamate agonist quinolinic acid (QUIN) (Schwarcz et al, 1984;Guidetti et al, 2006), the neuroprotectant and glutamate antagonist kynurenic acid (KYNA) (Schwarcz et al, 1983;Yu et al, 2004), and the redox active metabolites 3-hydroxykynurenine (3-HK) and 3-hydroxyanthranilic acid (3-HAAO) (Goldstein et al, 2000;Braidy et al, 2009;reviewed by Colín-González et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Although 3HAA, 3HK, and QA at low concentrations signifi cantly increase intracellular NAD + levels, at concentrations exceeding 100 nM, they cause a dose-dependent decrease in intracellular NAD + levels. Likewise to NAD + depletion, higher concentrations of anthranilic acid may also cause cell death (Braidy et al 2009a ). Competitive inhibition of IDO activity with 1-methyl-l -tryptophan results in a dose-dependent decrease in intracellular NAD + levels and sirtuin deacetylase-1 (silent mating type information regulation 2 homolog-1, SIRT1) activity.…”
Section: Toxic Versus Protective Effect Of Tryptophan Metabolitesmentioning
confidence: 99%